Therapeutic Potential of Ginger Exosome-Like Nanoparticles for Alleviating Periodontitis-Induced Tissue Damage - Xie Q; Gu J; Sun Y; Hong J; Wang J; Li N; Zhang Y; Liu M; Zhang X; Zhao X; Chen X; Wang X (International Journal of Nanomedicine, 2024)
Qingpeng Xie,1,2,* Jiawen Gu,1,2,* Yujia Sun,3 Jinjia Hong,1,2 Jia Wang,1,2 Na Li,1,2 Yuan Zhang,1,2 Meixian Liu,1,2 Xiaoxuan Zhang,1,2 Xiangyu Zhao,1,2 Xiaohang Chen,1,2 Xing Wang1,2 1Shanxi Medical University School and Hospital of Stomatology, Taiyuan, 030001, People’s Republic of China; 2Shanxi Province Key Laboratory of Oral Diseases Prevention and New Materials, Taiyuan, 030001, People’s Republic of China; 3Nursing College of Shanxi Medical University, Taiyuan, 030001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaohang Chen; Xing Wang, Shanxi Medical University School and Hospital of Stomatology, Taiyuan, 030001, People’s Republic of China, Tel +8618834896163 ; +8613934224604, Email kqyx__cxh@163.com; wangxing@sxmu.edu.cnPurpose: Periodontitis is a chronic inflammatory oral disease that causes defects in periodontal tissue. Conventional therapies are limited, and often lead to high recurrence rates. The emerging concept of medicinal food homology has shed light on the potential of ginger as a therapeutic adjuvant for periodontitis, given its antioxidant and anti-inflammatory properties. However, fresh ginger exhibits poor stability and bioavailability. Ginger exosome-like nanoparticles (GELNs), a derivative of ginger, have not been reported to exert therapeutic effects in periodontitis. This study aimed to explore the therapeutic effects of GELNs on tissue damage caused by periodontitis and their underlying mechanisms of action.Methods: The GELNs composition was analyzed using a widely targeted metabolome. Stability was assessed using nanoparticle tracking analysis (NTA) and zeta potential measurements, flavor was evaluated using an electronic nose, and membrane penetration was studied using confocal microscopy. A periodontitis model was established in SD rats, periodontal clinical indicators were monitored, and histological changes were assessed using H&E and TRAP staining. Co-culture experiments investigate the antioxidant and reparative abilities of GELNs on periodontal ligament fibroblasts (PDLFs) in inflammatory environment. NF-κB protein expression was examined by immunofluorescence and immunohistochemistry.Results: The findings revealed that GELNs demonstrated good stability in different environments and mitigated the pungent taste of the raw ginger. In vivo experiments showed that GELNs improved periodontal clinical parameters and pathology compared with ginger juice. In vitro data suggested that GELNs enhanced the proliferation and migration of PDLFs while reducing the reactive oxygen species (ROS) levels by inhibiting the NF-κB signaling pathway in an inflammatory setting.Conclusion: This study is the first to demonstrate that GELNs have a potential therapeutic effect on periodontitis. GELNs can alleviate oxidative stress (OS) and inflammatory reactions by inhibiting the NF-κB signaling pathway. These findings provide a promising method for the treatment of periodontitis by regulating an unbalanced OS state. Keywords: ginger exosome-like nanoparticles, periodontitis, tissue repair, oxidative stress, periodontal ligament fibroblasts